Development of color standards for roasted peanuts - Santiago, Kristine Flores
Color standards were developed for roasted peanuts. L, a, b values were determined for peanuts roasted at 140°C and 170°C for different time periods. Consumer acceptability tests were conducted to determine the most acceptable roast using 24 panelists. Lightness of roasted peanuts decreased with prolonged roasting (L = 76.54 for raw peanuts to L = 47.73 for peanuts roasted at 170°C for 60 minutes). Roasted peanuts acceptable to consumers may be produced by roasting at 140°C for 30 minutes.